(untitled) (Scientific journal of the Fergana State University, 2024)
The anthropocentric paradigm of modern methods of teaching foreign languages ​​is aimed at shaping the student’s personality, creating conditions for his self-awareness and development in the social and professional spheres. In this regard, a student-centered approach to learning comes to the fore. In our case, foreign language education is focused on the personality of a bilingual student. The thesaurus approach to teaching future teachers’ professional communication in a foreign language helps to form a professional thesaurus in a foreign language as a body of knowledge in pedagogy. A terminological dictionary of the thesaurus type is used as a structured form of a professional thesaurus in the educational process.